Trades access common core. Line D. Organizational skills; Competency D-6 Plan projects - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"Every job is different and may have special requirements. Anticipating these requirements and planning accordingly is vital to ensuring that you have the materials, tools, and time to complete the job. To do this effectively you will need to have a clear understanding of the overall job. You will need to know what materials are required and be able to record organized and accurate notes on the time and materials used when the job is complete. Planning ahead saves time and money and makes a job more profitable. Effectively managing time and resources, including materials, and keeping detailed notes is very important whether you are working for another company or on your own. It allows your company to be more competitive and also provides a good base for estimating the costs of similar jobs in the future"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Standards, Engineering -- Textbooks; Electronic books